2019
DOI: 10.3389/fimmu.2019.00065
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Vitamin D Supplementation on Influenza Vaccine Response and Immune Functions in Deficient Elderly Persons: A Randomized Placebo-Controlled Trial

Abstract: Background: Immunosenescence contributes to reduced vaccine response in elderly persons, and is worsened by deficiencies in nutrients such as Vitamin (Vit-D). The immune system is a well-known target of Vit-D, which can both potentiate the innate immune response and inhibit the adaptive system, and so modulate vaccination response.Objective: This randomized placebo-controlled double-blind trial investigated whether Vit-D supplementation in deficient elderly persons could improve influenza seroprotection and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
122
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(130 citation statements)
references
References 57 publications
4
122
0
4
Order By: Relevance
“…Specifically, these studies show that oral vitamin D in very large doses upregulates TLR2, TLR4, IL-17A, CCR4, CXCR4, IL12RB1, IL12RB2, and TGF beta. 107,109,112,113,115 The upregulation of each of these has also been observed in CD. 99,108,110,111,114 While the doses involved in these studies are very large, the direction of association suggests that in those whose plasma levels of 1,25(OH) 2 D are already elevated or are predisposed to elevation, more modest doses of oral vitamin D may induce a state of increased immune activation that puts such individuals at greater risk for onset of CD.…”
Section: Select Effects Of Vitamin D On the Immune Systemmentioning
confidence: 85%
“…Specifically, these studies show that oral vitamin D in very large doses upregulates TLR2, TLR4, IL-17A, CCR4, CXCR4, IL12RB1, IL12RB2, and TGF beta. 107,109,112,113,115 The upregulation of each of these has also been observed in CD. 99,108,110,111,114 While the doses involved in these studies are very large, the direction of association suggests that in those whose plasma levels of 1,25(OH) 2 D are already elevated or are predisposed to elevation, more modest doses of oral vitamin D may induce a state of increased immune activation that puts such individuals at greater risk for onset of CD.…”
Section: Select Effects Of Vitamin D On the Immune Systemmentioning
confidence: 85%
“…Other studies have demonstrated the role of Vit D in regulating the immune system. Vit D may suppress cytokine production by simultaneously boosting the innate immune system and reducing the overactivation of the adaptive immune system in response to viral load [11,13]. Vit D deficiency may be more prevalent among the elderly and African-American [8] but it includes every population group.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have suggested the potential role of Vit D in suppressing cytokine storm during the 1918-1919 viral influenza pandemic [12]. Moreover, the role of Vit D in enhancing immune response in flu and previous coronaviruses has been suggested [11,13]. It is this ability of Vit D in suppressing cytokine production [14,15]that motivated our focus on Vit D deficiency and its association with severe COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Related clinical research studies are warranted. Based on numerous studies of other viruses [45,46], it is reasonable to hypothesize that vitamins C and D supplementation may boost immunity and help human organism fight COVID-19 and its aggressive effects on all organ systems (Fig. 1).…”
Section: Manifestations Of Covid-19 Which May Mimic Rheumatic Diseasesmentioning
confidence: 99%